Teologi Gender: Kepemimpinan Perempuan dalam Rumah Tongkonan di Balusu, Kabupaten Toraja Utara - Vivilia TandiPadang (Kamarampasan: Jurnal Mahasiswa Kepemimpinan Kristen, 2023)
Abstract: This paper aims to examine women’s leadership in Tongkonan traditional house in Balusu from the perspective of gender theology. This study uses a qualitative approach with ethnographic research. The involvement of women in the public sector in Balusu is the reason the outhor is interested in studying women’s leadership in Tongkonan in Balusu. Gender equality is an equal condition between men and women, including equality in obtaining the right to lead. The leadership of Tongkonan plays an important role in life of Tongkonan. The women leaderdship in Tongkonan is a leadership that is oriented to the wider community in accordance with the customary area. The women leadership in Balusu is leadership that focuses on the welfare of the people. This leadership is plays the role of a mother who faces all situations and conditions that occur in society with courage, patience, humility, wisdom and fairness.   Keywords: Equality, Leadership, Women, Tongkonan.   Abstrak: Tulisan ini bertujuan untuk mengkaji kepemimpinan perempuan dalam rumah adat tongkonan di Balusu yang ditinjau dari perspektif teologi gender. Penelitian ini menggunakan pendekatan kualitatif dengan penelitian etnografi. Keterlibatan perempuan pada sektor publik di Balusu menjadi alasan penulis tertarik untuk  mengkaji kepemimpinan perempuan dalam rumah adat tongkonan di Balusu. Kesetaraan gender merupakan kondisi setara antara laki-laki dan perempuan, diantaranya kesamaan untuk memperoleh hak memimpin.  Kepemimpinan rumah adat tongkonan berperan penting bagi kehidupan tongkonan. Kepemimpinan perempuan dalam rumah adat tongkonan di Balusu adalah kepemimpinan yang berorientasi pada masyarakat luas sesuai dengan kawasan adat. Kepemimpinan perempuan dalam rumah adat tongkonan di Balusu merupakan kepemimpinan yang berfokus pada kesejahteraan rakyatnya. Kepemimpinan tersebut merupakan kepemimpinan yang berperan sebagai ibu yang menghadapi segala situasi dan kondisi yang terjadi di tengah masyarakat dengan penuh keberanian, kesabaran, rendah hati, bijaksana dan adil. Kata kunci: Kesetaraan, Kepemimpinan, Perempuan, Tongkonan.